Snack Consumption Behavior and Tooth Decay-Related Pain during Corona Virus Disease-19 Pandemic - Palupi, Retno; Fakhrunnisa, Dania Artha; Sya'bania, Asma'; Az-Zahra, Fatiha (Indonesian Journal of Dental Medicine, 2025)
Background: The corona virus disease-19 (COVID-19) pandemic has greatly affected community lives. The self-quarantine has an impact on the occurrence of psychological stress and the tendency to consume snacks.  Dentist practice activities are limited in order to avoid the spread of this virus. As a result, oral and dental health is less controlled, and the habit of consuming cariogenic snacks during the pandemic increases the risk of dental problems. Purpose: This study aimed to analyze the correlation between snack consumption behavior and tooth decay-related pain complaints in the productive age population during the COVID-19 pandemic. Methods: This study design was an analytic observational study with a cross-sectional approach. The data collection used online questionnaires in the form of Google Forms to obtain the answer to snack consumption behavior. The population of this study was a productive age group population who lived in Surabaya. The total number of respondents in this study was 163 people. Results: The correlation test result showed a significant correlation (p < 0.05) between the snack consumption behavior and tooth decay-related pain, but there was no significant correlation between the snack consumption behavior and the habit of maintaining oral health. Conclusion: During the COVID-19 pandemic, there was an increase in snack consumption that leads to tooth decay-related pain complaints in the age-productive population in Surabaya.